2002
DOI: 10.1002/hrm.10031
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and optimizing multisource feedback

Abstract: Three-hundred-and-sixty degree or multisource feedback, the process in which subordinates, peers, supervisors, and/or customers provide anonymous feedback to recipients, has grown in popularity over the past decade (Waldman & Atwater, 1998). In 1993, HRMJ published a special issue that included articles addressing topics such as 360-degree feedback as a competitive advantage, the impact of such feedback on management skills development, and suggestions for boosting the power of peer ratings. In July 1995, The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
67
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(72 citation statements)
references
References 34 publications
5
67
0
Order By: Relevance
“…One of the reasons for its growing popularity is its perceived potential for generating more objective assessments of employee performance (Atwater, Waldman and Brett, 2002;Boice and Kleiner, 1997) particularly when compared to the constraints of one-way feedback that characterises organisational practice (Garavan, Morley and Flynn, 1997). Mount and Judge (1998) characterise 360-degree feedback systems as an evaluation of an individual's performance by multiple raters from multiple levels in the organisation.…”
Section: -Degree Appraisalmentioning
confidence: 99%
“…One of the reasons for its growing popularity is its perceived potential for generating more objective assessments of employee performance (Atwater, Waldman and Brett, 2002;Boice and Kleiner, 1997) particularly when compared to the constraints of one-way feedback that characterises organisational practice (Garavan, Morley and Flynn, 1997). Mount and Judge (1998) characterise 360-degree feedback systems as an evaluation of an individual's performance by multiple raters from multiple levels in the organisation.…”
Section: -Degree Appraisalmentioning
confidence: 99%
“…In other words, achieving the reduced perceptual discrepancies is not an end in itself; just as important is the positive impact it can have on personal and employee outcomes (Hollenbeck, 1989;Phillips, Hollenbeck, & Ilgen, 1996). Thus, managerial behaviors and actions improved through the self-awareness coaching intervention should not only be recognized by others (discrepancy reduction), but should also result in improved attitudes of the target managers themselves-since they became aware of the facts, learned how to evaluate them, and developed effective behavioral responses-and better attitudes of their employees -since, due to the change in managerial behaviors and actions, they operate under more effective managers and thus have a favorable attitudinal reaction (Atwater, Waldman, Atwater, & Cartier, 2000;Atwater et al, 2002;Tsui & Ashford, 1994).…”
Section: Background Of the Studymentioning
confidence: 99%
“…As managerial jobs become more complex and multidimensional (London & Beatty, 1993;Varma, Beatty, Schneier, & Ulrich, 1999), organizations are increasingly implementing high-performance work practices such as 360-degree feedback interventions in hopes of improving workplace attitudes and performance (Atwater, Waldman, & Brett, 2002;London, 1997;London & Smither, 1995;Tornow & London, 1998). A very recent large survey found that about one in five firms currently use 360s (Armour, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Various authors have pointed out that merely reading an analysis of ratings by students or being aware of weaknesses does not automatically incite teachers to reflect on and look for ways to improve their teaching practice (Atwater et al 2002;Seifert et al 2003;Smither et al 2005). Moreover, there is evidence that unfacilitated feedback can cause negative emotional reactions, like denial and defensiveness, which can even raise barriers to reflection (DeNisi & Kluger 2000;Sargeant et al 2008;Overeem et al 2009) and behavioural change (Sargeant et al 2008).…”
Section: Introductionmentioning
confidence: 99%